LEGO as an investment opportunity : Developing a price comparison platform for maximizing returns on LEGO sets - Kachanov, Andrei (2025)
This master’s thesis explores the potential of LEGO sets as a non-financial investment asset and addresses the challenges faced by individuals who want to start investing in them. While LEGO has proven to be a surprisingly profitable collectible, the market is often hard to navigate due to price fragmentation, lack of standardized evaluation, and the presence of counterfeit products. The main objective of this work was to design and develop a proof-of-concept (PoC) web platform that compares LEGO set prices across multiple vendors and calculates an investment score based on selected financial and market factors. The platform, called brickseekr.com, provides users with tools to evaluate the investment potential of LEGO sets and make better purchasing decisions. The first part of the thesis focuses on the theoretical foundations of non-financial investments, the evolution of LEGO as an investment class, and the market mechanisms that influence its value. The second part is practical and describes the process of designing, developing, and validating the platform. It includes system architecture, backend and frontend implementation, API integrations, and UX principles. This thesis aims to make LEGO investing more accessible by providing a transparent and user-friendly tool that supports decision-making based on data rather than intuition or speculation.